2022
DOI: 10.1111/caim.12480
|View full text |Cite
|
Sign up to set email alerts
|

Decent work and innovative work behaviour: Mediating roles of work engagement, intrinsic motivation and job self‐efficacy

Abstract: In nowadays highly competitive and dynamic environment where employees' innovative work behaviour (IWB) has become critical source for business success, employees' quality of work lives is severely challenged by the global deregulated labour market. As an institutional effort to combat the challenges faced by labour world, the concept of decent work was proposed by International Labor Organization (ILO) in 1999, which is defined as work—and work‐related contexts—that provides adequate and fair income, social p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 88 publications
5
59
0
1
Order By: Relevance
“…Our participants were more likely to consider leaving their job due to autonomy-thwarting in the case of self-PMIEs. This is in line with previous research, which showed that perceived autonomy support at work decreases burnout, compassion fatigue and turnover intentions while also increasing work satisfaction, organizational identification, innovative behavior, work engagement and job performance [ 90 , 91 , 92 , 93 , 94 , 95 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our participants were more likely to consider leaving their job due to autonomy-thwarting in the case of self-PMIEs. This is in line with previous research, which showed that perceived autonomy support at work decreases burnout, compassion fatigue and turnover intentions while also increasing work satisfaction, organizational identification, innovative behavior, work engagement and job performance [ 90 , 91 , 92 , 93 , 94 , 95 ].…”
Section: Discussionsupporting
confidence: 92%
“…This result shows that creative self-efficacy as an intermediary variable can influence employee autonomy and engagement in innovation behaviour (Orth and Volmer, 2017). Xu et al (2022) points out that more decent work can increase employee engagement, and promote employee innovation behaviour through the mediation of self-efficacy, which also supports our verification results. Therefore, H5 is rejected and H9 is accepted.…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 83%
“…The background shows that self-efficacy leads to lower levels of emotional exhaustion (Salanova et al, 2002). Similarly, under the theory of self-determination (Deci and Ryan, 2000), self-efficacy improves workers' needs for autonomy and is recognized as a motivational variable that leads to workers' creativity (Ng and Feldman, 2012) and improves the quality of work life (Xu et al, 2022). Numerous studies confirmed the influence of self-efficacy on the quality of work life (Mensah and Lebbaeus, 2013;Orgambídez et al, 2020;Putra et al, 2021).…”
Section: Discussionmentioning
confidence: 99%